HUBUNGAN KEPUASAN KERJA DAN KINERJA PEGAWAI KOPERASI SAWIT MAHATO JAYA - Marsudi Marsudi; Yuritanto Yuritanto; Armansyah Armansyah (Jurnal Inovasi Penelitian, 2021)
The service process of an organization or organization does not release all existing resources, one of which is employees. Existing resources are always well managed so that they can provide new benefits or colors in the journey of a better organization or organization going forward. Various problems exist such as facilities, and employees who come from the organization or organization. For this reason, Job Satisfaction and Employee Performance is the main focus of attention and should be given more attention in order to achieve the goals of the organization or organization that have been set. The variables in this study are the Job Satisfaction Variable and Performance Variable. The sample in this study may be 30 employee respondents. The research was conducted at the Mahato Jaya Cooperative of Palm Oil, Mahato Village. This research aims to see the relationship between Job Satisfaction and Employee Performance. Data aids using online questionnaires and analyzed with SPSS 26 Statistics. The results of the study data analysis show that Job Satisfaction has a positive and significant relationship with Employee or Employee Performance. For future studies, conduct research by paying attention to other variables that are not examined in the research, for example; Work Environment and Organizational Commitment